1998
DOI: 10.3923/pjbs.1998.348.350
|View full text |Cite
|
Sign up to set email alerts
|

Response of Two Sunflower (Helianthus annuus L.) Cultivars To Different Levels of Nitrogen

Abstract: Response of two sunflower cultivars namely Aritar-93 and suncom-110 to N levels of 0, 50, 100 and 150 kg haG 1 was studied under field conditions. Sunflower cultivar suncom-110 produced significantly higher plant height, leaf area per plant, 1000-achene weight and achene yield. Plant height, leaf per plant, stem diameter, no. of achenes per disc and achene protein contents were maximum at N level of 150 kg haG 1 . Whereas, oil contents were significantly higher in control. Nitrogen application at 100 and 150 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
2
3
0
Order By: Relevance
“…The crude protein content increased up to 20-21% at the highest N rates, whereas it was 17-18% under the control treatment (0 kg ha -1 N). Our results are in agreement with those of Kassem and El-Mesilby (1992), Ayup et al (1998), andOzer et al (2004) who stated that the protein content increased with increasing N rates, whereas the oil content decreased significantly. In contrast, our findings do not correspond with those of Steer et al (1986), and Oyinlola et al (2010) who reported that the oil content of sunflower seeds were increased by nitrogen fertilizers.…”
Section: Notes Ni -Non-irrigated I -Irrigated Y -Year B -Blocks (supporting
confidence: 83%
See 4 more Smart Citations
“…The crude protein content increased up to 20-21% at the highest N rates, whereas it was 17-18% under the control treatment (0 kg ha -1 N). Our results are in agreement with those of Kassem and El-Mesilby (1992), Ayup et al (1998), andOzer et al (2004) who stated that the protein content increased with increasing N rates, whereas the oil content decreased significantly. In contrast, our findings do not correspond with those of Steer et al (1986), and Oyinlola et al (2010) who reported that the oil content of sunflower seeds were increased by nitrogen fertilizers.…”
Section: Notes Ni -Non-irrigated I -Irrigated Y -Year B -Blocks (supporting
confidence: 83%
“…Ozer et al (2004) reported that the head diameter was 20.7 and 20.6 cm for N rates of 120 and 160 kg ha -1 N, respectively, whereas it was 18.5 cm under the control treatment. Our results for the plant height and head diameter are in close agreement with those of Robinson et al (1979), Ayup et al (1998), Sadiq et al (2000), Malik et al (2004), andOzer et al (2004).…”
Section: Notes Ni -Non-irrigated I -Irrigated Y -Year B -Blocks (supporting
confidence: 82%
See 3 more Smart Citations